2012
DOI: 10.1016/j.jmb.2011.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Domain Flexibility Modulates the Heterogeneous Assembly Mechanism of Anthrax Toxin Protective Antigen

Abstract: Individually, the three protein components of anthrax toxin are nontoxic, but when they assemble, they form active holotoxin complexes. The role of the protective antigen (PA) component of the toxin is to deliver the two other enzyme components, lethal factor (LF) and edema factor (EF), across the plasma membrane and into the cytoplasm of target cells. PA is produced as a proprotein, which must be proteolytically activated, and generally cell-surface activation is mediated by a furin-family protease. Activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 79 publications
1
36
0
Order By: Relevance
“…The staphylococcal ␣-hemolysin has been shown to form heptamers but under certain conditions will also form hexameric rings (25). Anthrax toxin was long thought to form heptamers exclusively (9), but the work by Krantz and colleagues (10,11,26,27) has shown that functional octamers can also be formed, a conclusion that is confirmed and extended by these studies. This suggests a cautionary approach when considering the oligomeric states of other anthrax-like toxins, such as clostridial C2 toxin and iota toxin (28), and even all other pore-forming toxins, to include consideration that alternative oligomeric forms might be present in certain situations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The staphylococcal ␣-hemolysin has been shown to form heptamers but under certain conditions will also form hexameric rings (25). Anthrax toxin was long thought to form heptamers exclusively (9), but the work by Krantz and colleagues (10,11,26,27) has shown that functional octamers can also be formed, a conclusion that is confirmed and extended by these studies. This suggests a cautionary approach when considering the oligomeric states of other anthrax-like toxins, such as clostridial C2 toxin and iota toxin (28), and even all other pore-forming toxins, to include consideration that alternative oligomeric forms might be present in certain situations.…”
Section: Discussionmentioning
confidence: 87%
“…Comparison of the octamer and heptamer crystal structures revealed that there are two orientations of PA domain 4 (the receptor-binding domain) that alternate in the octamer to accommodate the new geometry. Constraining the location of PA domain 4 using different linkers connected to the remainder of the protein altered the proportion of octamers and heptamers (11).…”
mentioning
confidence: 99%
“…3 B and C). The per-residue deviations of 4EE2 relative to 3TEW (30) (Fig. S4) are largest in D2 and D4 (>1 Å).…”
mentioning
confidence: 98%
“…3B). These loops include the furin-proteolysis site (residues 162-174) [also modeled in the 1.45-Å PA structure 3TEW (30)] and some of the β-barrel residues, 276-287 and 343-350 (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation